Utilizing Shift-or-Shrink Method to Optimize Multisegment Structures of Bent Optical Waveguides - Lu,Ruei-Chang (2019)
Abstract The authors utilized a heuristic shift-or-shrink method that is associated with the beam propagation method to design an optimal multisegment bent optical waveguide. By transforming the shape of each segment, the multisegment structure of the bent waveguide can be optimized. In addition to achieving maximal transmission efficiency, only four segments are sufficient to satisfactorily improve the transmission performance. Moreover, the optimal path of each of these multisegment bent waveguides remains similar to each other waveguide's optimal path even though the number of the segments increases.